Microsoft windows security resource kit - Smith, Ben, 1975- (Microsoft Press, 2005)
Fully updated and revised, this official MICROSOFT RESOURCE KIT delivers the in-depth information and tools you need to plan and implement a comprehensive security-management strategy for Windows-based clients, servers, and networks.